Bat distribution size or shape as determinant of viral richness in african bats - Maganga, Gaël D; Bourgarel, Mathieu; Vallo, Peter; Dallo, Thierno D; Ngoagouni, Carine; Drexler, Jan Felix; Drosten, Christian; Nakouné, Emmanuel R; Leroy, Eric M; Morand, Serge (PloS one, 2014)
The rising incidence of emerging infectious diseases (EID) is mostly linked to biodiversity loss, changes in habitat use and increasing habitat fragmentation. Bats are linked to a growing number of EID but few studies have explored the factors of viral richness in bats. These may have implications for role of bats as potential reservoirs. We investigated the determinants of viral richness in 15 species of African bats (8 Pteropodidae and 7 microchiroptera) in Central and West Africa for which we provide new information on virus infection and bat phylogeny. We performed the first comparative analysis testing the correlation of the fragmented geographical distribution (defined as the perimeter to area ratio) with viral richness in bats. Because of their potential effect, sampling effort, host body weight, ecological and behavioural traits such as roosting behaviour, migration and geographical range, were included into the analysis as variables. The results showed that the geographical distribution size, shape and host body weight have significant effects on viral richness in bats. Viral richness was higher in large-bodied bats which had larger and more fragmented distribution areas. Accumulation of viruses may be related to the historical expansion and contraction of bat species distribution range, with potentially strong effects of distribution edges on virus transmission. Two potential explanations may explain these results. A positive distribution edge effect on the abundance or distribution of some bat species could have facilitated host switches. Alternatively, parasitism could play a direct role in shaping the distribution range of hosts through host local extinction by virulent parasites. This study highlights the importance of considering the fragmentation of bat species geographical distribution in order to understand their role in the circulation of viruses in Africa.
Keywords: Population Density; Animals; Viruses; Population Dynamics; Communicable Diseases, Emerging; biodiverzita; cytochromy b; Geography; Disease Reservoirs; zdroje nemoci; Chiroptera; Afrika; viry; objevující se infekční nemoci; hustota populace; Cytochromes b; zeměpis; Phylogeny; Africa; Biodiversity; populační dynamika; zvířata; fylogeneze